Calibration and cross‐validation of a wrist‐worn Actigraph in young preschoolers. Issue 1 (10th January 2014) - Johansson, E.; Ekelund, U.; Nero, H.; Marcus, C.; Hagströmer, M.
Summary Objective To calibrate the Actigraph GT3X+ accelerometer for wrist‐worn placement in young preschoolers by developing intensity thresholds for sedentary, low‐ and high‐intensity physical activity. Furthermore, to cross‐validate the developed thresholds in young preschoolers. Methods Actigraph GT3X+ was used to measure physical activity during structured activities and free play in 38 children (15–36 months). Activity was video recorded and scored into sedentary, low‐ and high‐intensity physical activity based on Children's Activity Rating Scale (CARS) and combined with accelerometer data using a 5 s epoch. Receiver operating characteristic analysis was used to develop intensity thresholds in 26 randomly selected children. The remaining 12 children were used for cross‐validation. Results Intensity thresholds for sedentary were ≤89 vertical counts (Y) and ≤221 vector magnitude (VM) counts per 5 s and ≥440 Y counts and ≥730 VM counts per 5 s for high‐intensity physical activity. Sensitivity and specificity were 60–100% for the developed intensity thresholds. Strong correlations (Spearman rank correlation 0.69–0.91) were found in the cross‐validation sample between the developed thresholds for the accelerometer and CARS scoring time in all intensity categories. Conclusion The developed intensity thresholds appear valid to categorize sedentary behaviour and physical activity intensity categories in children 2 years of age.